Changes in peripheral and central sensitization in patients undergoing occipital nerve stimulation. Issue 4 (November 2020) - Wodehouse, Theresa; Bahra, Anish; Mehta, Vivek
Introduction: Central sensitization and impaired conditioned pain modulation (CPM) response have been reported to contribute to migraine progression. Migraine patients can present with allodynia possibly attributed to increased sensitivity of peripheral ends of nociceptors with both peripheral and central sensitization. Occipital nerve stimulation (ONS) works by stimulating the distal branches of C1, C2 and C3 possibly altering the nociceptive traffic to the trigemino-cervical complex, brainstem and supranuclear connections. Aims: This observational study explores peripheral and central sensitization in patients undergoing percutaneous ONS. Methods: Following local regulatory approval, 13 patients undergoing ONS with dual Octrode 90 cm leads and rechargeable implantable pulse generator (IPG) (St Jude) were recruited to have quantitative sensory testing (QST) pre- and post-procedure 2 weeks, 1, 3, 6 and 12 months. Results: Patients with intractable migraine demonstrated impaired CPM (mean baseline pressure pain thresholds (PPTs): 61.98 kPa vs 48.01 kPa cuff inflated) prior to ONS, reverting to an efficient CPM response within 2 weeks following ONS implant (68.9 kPa vs 104.5 kPa cuff inflated) and continuing positively over the next 12 months. In contrast, no statistical difference was observed in PPTs. Conclusion: This is the first reported observation highlighting the effects on central sensitization following ONS. A consistent and sustained improvement in CPM was observed in contrast to PPT's where there was no difference. Normalisation of the CPM response following ONS indicates that the treatment may reduce central sensitization in the migraine population.